Pengaruh Kepemimpinan terhadap Kinerja Perangkat Desa dengan Kepuasan dan Komitmen Sebagai Variabel Mediasi - Deva Budyawan; Edward Edward; Sigit Indrawijaya (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to examine and analyze the influence of leadership on the performance of village officials by using two mediations at once in the form of commitment and job satisfaction. This research method uses a quantitative research approach. This study was designed using survey research techniques. The population used in this study were village officials from 7 villages in Pulau Tengah, Keliling Danau District, Kerinci Regency. The data analysis technique used is descriptive analysis technique and Partial Least Squares (PLS). The results obtained are, firstly, based on the results of leadership testing, it has a positive and significant effect on job satisfaction in 7 villages in Pulau Tengah, Kerinci district. Second, based on testing the results of leadership have no effect on organizational commitment. Third, based on the results of the PLS test, the leadership variable of the village head affects the performance of the village apparatus. Fourth, based on the results of this study, it shows that based on the results of testing job satisfaction has a significant effect on the performance of village officials. Fifth, the results obtained that organizational commitment affects the performance of village officials. Sixth, research shows a significant influence of leadership on performance mediated by satisfaction. Seventh, research shows that leadership has no effect on performance mediated by organizational commitment.